Perencanaan Jembatan Beton Prategang Way Pengubuan Lampung Tengah (Ruas Terbanggi Subing-Gunung Sugih) - Alexander, Yogi; Purba, Aleksander; Herianto, Dwi (Universitas Lampung, 2019)
This thesis discusses the analysis of the Way Pengubuan bridge that connects the Gunung Sugih and Terbanggi Subing regions which are separated by rivers and have bridges that have not yet fulfilled the feasibility of being a bridge completely. So that the Government made the Way Pengubuan bridge construction project which aims to facilitate community mobilization so that the community's economy can increase. The location of this study was carried out on Way Pengubuan bridge, Gunung Sugih - Terbanggi Subing, Lampung Tengah Regency, Lampung Province. The data needed during this research are planning standards issued by SNI, literature published bridge planning standards, and general bridge data obtained from P.T. YODYA KARYA (Persero) as a project contractor. The method carried out in this study is to use the data obtained then analyze the structure of the bridge, analyze the structure of the structure under the bridge. From the results of the study it can be seen that the type of bridge used is prestressed concrete with a total span of 80 m, the span between abutments and 40m pillars, 7m bridge width, 2x3.5m track width, and 2m sidewalk width, Reinforcing bar on Pier and Abutment heads using Main Reinforcing bar D19, Reinforcing bar on Pier & Abutment Body using Main Reinforcing bar D25-250, Reinforcement on Abutment Feet using Reinforcing bar D22-50 meanwhile on Pier Foot uses Main Reinforcing bar D25-125.